Molecular and expressional characterization of tumor heterogeneity in pulmonary carcinosarcoma. Issue 10 (18th July 2022) - Ohtaki, Yoichi; Kawabata‐Iwakawa, Reika; Nobusawa, Sumihito; Goto, Yusuke; Shimizu, Kimihiro; Yajima, Toshiki; Nakazawa, Seshiru; Kawatani, Natsuko; Yoshida, Yuka; Sano, Takaaki; Shirabe, Ken
Abstract: The genetic concordance and heterogeneity of the two components of pulmonary carcinosarcoma (PCS), carcinoma, and sarcoma, have not been fully elucidated because of its rare occurrence. We performed targeted sequencing of the carcinoma and sarcoma components of four PCSs to identify genetic similarities and differences. Formalin‐fixed paraffin‐embedded tissue samples were macroscopically or microscopically dissected. DNA was extracted from each component, and genetic alterations were analyzed separately. Moreover, we performed RNA‐seq analysis on both components of one PCS to compare differences in gene expression profiles. The carcinoma part consisted of adenocarcinoma in two cases, squamous cell carcinoma in one, and adenosquamous carcinoma in the last. TP53 mutation was observed in three samples from the trunk, although it was detected only in the sarcoma part in one case. No specific driver gene mutation was observed; however, KRAS mutations were observed in one case in the trunk. RNA‐seq analysis revealed that the rhabdomyosarcoma component expressed various genes related to muscle development, whereas the carcinoma component did not; and that gene expression overall was completely different between the two components. Our study revealed that the two different components of PCS shared common gene mutations in most cases. Although gene expression was different among components, if driver genes such as KRAS were detected in PCS, molecular targeted therapy could be beneficial even when the tumor contains a sarcoma component.